P363 HIGH–SENSITIVITY TROPONINS FOR OUTCOME PREDICTION IN THE GENERAL POPULATION: A SYSTEMATIC REVIEW AND META–ANALYSIS. (18th May 2022) - Aimo, A; Georgiopoulos, G; Panichella, G; Vergaro, G; Passino, C; Emdin, M; Clerico, A
Abstract: Background: High–sensitivity (hs) assays allow to measure cardiac troponin T and I (cTnT/I) even in healthy individuals. The higher hs–cTn values, the higher the ongoing cardiomyocyte damage, and then reasonably the risk of developing symptomatic cardiac disease. Methods: We retrieved all studies evaluating the prognostic value of hs–cTnT or I in the general population. We calculated pooled hazard ratio (HR) values for all–cause and cardiovascular death, cardiovascular events and heart failure (HF) hospitalization. Results: We included 24 studies for a total of 203, 202 subjects; 11 studies assessed hs–cTnT and 14 hs–cTnI. One standard deviation (SD) increase in baseline hs–cTn was associated with a 23% higher risk of all–cause death (HR 1.226, 95% CI 1.083–1.388, p < 0.001, I2=88.5%); all these studies measured hs–cTnI. In an exploratory analysis on 3 studies with 25, 760 subjects, hs–cTn predicted cardiovascular death (HR 1.822, 95% CI 1.241–2.674, p = 0.002, I2=87.2%). After synthesizing 9 studies with 58, 565 subjects, hs–cTn predicted cardiovascular events (HR 1.328, 95% CI 1.167–1.513, p < 0.001, I2=93.8%). Both hs–cTnT (HR 1.627, 95% CI 1.145–2.311, p < 0.001) and hs–cTnI (HR 1.260, 95% CI 1.115–1.423, p < 0.001; p for interaction <0.001). Furthermore, in 10 studies with 61, 467 subjects, hs–cTn predicted HF hospitalization (HR 1.493, 95% CI 1.368–1.630, p < 0.001, I2=76.6%). Both hs–cTnT (HR 1.566, 95% CI 1.303–1.883, p < 0.001) and hs–cTnI (HR 1.467, 95% CI 1.321–1.628, p < 0.001) were associated with HF hospitalization (p for interaction <0.001). Conclusions: Hs–cTn values hold strong prognostic value in subjects from the general population, predicting the risk of all–cause and cardiovascular mortality, cardiovascular events, and HF hospitalization.